Bradyrhizobium Inoculation Improved Agrosymbiotic Performances of Cowpea [Vigna unguiculata (L) Walp] Varieties at Two Sites in Ethiopia - Lemlem Yohannes; Tarekegn Yoseph; Tewodros Ayalew (International Journal of Agronomy)
Cowpea [Vigna unguiculata (L) Walp] is an important crop that protects soil fertility, supplements protein deficiency, and provides food security in the face of climate change. However, its productivity in the study area is low due to a lack of high-yielding varieties, high cost of mineral fertilizer, insufficient information on effective inoculum, and inadequate management practices. Therefore, this study aimed to assess the agrosymbiotic response of inoculated cowpea varieties at Dale and Hawassa sites in Ethiopia. A factorial combination of four cowpea varieties (Bole, TVU, Keti, and White Wonderer Trailing) and two inoculation levels (uninoculated and strain CP-24 inoculated) were evaluated in two experimental sites using a randomized complete block design with three replications. The results revealed that phenology, nodulation, growth, yield, and yield components differed significantly (P<0.05) among the tested cowpea varieties. Among the varieties, the White Wonder Trailing produced the highest grain yield of 2.98 t ha−1. The influence of Bradyrhizobium strain CP-24 was apparent in most of the studied parameters, except for days to emergence and harvest index. It increased cowpea grain yield by 28.47% compared to the control. The interaction of variety and Bradyrhizobium inoculation revealed a significant effect on nodule number, effective nodules, leaf area (LA), leaf area index (LAI), root dry weight, root length, pod length, aboveground biomass yield, and straw yield. Grain yield was strongly and markedly related to all parameters except for the harvest index. The partial budget analysis revealed that the White Wonder Trailing with inoculation provided the highest net benefit of 67171.3 Ethiopian Birr (ETB) ha−1, with a marginal rate return of 1386.7%. Therefore, using Bradyrhizobium strain CP-24 in combination with the White Wonder Trailing variety is highly recommended to increase cowpea yield and generate higher economic returns in the research sites and similar agroecological areas.